Cast Out Vagrancy and Homelessness in Global and Historical Perspective - Beier, A.L; Ocobock, Paul (Ohio University Press, 2008)
Throughout history, those arrested for vagrancy have generally been poor men and women, often young, able-bodied, unemployed, and homeless. Most histories of vagrancy have focused on the European and American experiences. This is the first book to consider global laws, homelessness, and the historical processes they accompanied. Vagrancy and homelessness are used to examine the migration of labor, social and governmental responses, poverty through charity, welfare, and prosecution. Cast Out includes discussions of the lives of the underclass, strategies for surviving and escaping poverty, the criminalization of poverty by the state, the rise of welfare and development programs, the relationship between imperial powers and colonized peoples, and the struggle to achieve independence after colonial rule.